Economics of using rbsT - Smith, John F., 1962- (Kansas Agricultural Experiment Station, 2011)
As new technologies such as rbST become available to dairy producers, evaluating the profitability of those technologies on individual farms is essential. Costs associated with rbST include purchase of product, feed, and labor. The costs of product and labor are independent of milk response. However, feed cost will increase as the milk production response to rbST increases. If the mailbox milk price is $10, approximately 7 lb more milk per day will be required to break even. It is essential that dairy producers have the management in place to achieve a profitable milk response to rbST.
Keywords: Recombinant bovine; somatotropin; Economics